Current concepts in diagnosis and management of common upper limb nerve injuries in children. (April 2021) - Catena, Nunzio; Gennaro, Giovanni Luigi Di; Jester, Andrea; Martínez-Alvarez, Sergio; Pontén, Eva; Soldado, Francisco; Steiger, Christina; Choong, Jiahui; Zarantonello, Paola; Farr, Sebastian; ,
Abstract: Peripheral nerve injuries (PNI) of the upper limb are a common event in the paediatric population, following both fractures and soft tissues injuries. Open injuries should in theory be easier to identify and the repair of injured structures performed as soon as possible in order to obtain a satisfying outcome. Conversely, due to the reduced compliance of younger children during clinical assessment, the diagnosis of a closed nerve injury may sometimes be delayed. As the compliance of patients is influenced by pain, anxiety and stress, the execution of the clinical manoeuvres intended to identify a loss of motor function or sensibility, can be impaired. Although the majority of PNI are neuroapraxias resulting in spontaneous recovery, there are open questions regarding certain aspects of closed PNI, e.g. when to ask for electrophysiological exams, when and how long to wait for a spontaneous recovery and when a surgical approach becomes mandatory. The aim of the article is therefore to analyse the main aspects of the different closed PNI of the upper limb in order to provide recommendations for timely and correct management, and to determine differences in the PNI treatment between children and adults.